2021
DOI: 10.1002/hep4.1686
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic Acid‐Derived Oxylipins Differentiate Early Stage Alcoholic Hepatitis From Mild Alcohol‐Associated Liver Injury

Abstract: Alcohol-associated liver disease (ALD) is a spectrum of liver disorders ranging from steatosis to steatohepatitis, fibrosis, and cirrhosis. Alcohol-associated hepatitis (AH) is an acute and often severe form of ALD with substantial morbidity and mortality. The mechanisms and mediators of ALD progression and severity are not well understood, and effective therapeutic options are limited. Various bioactive lipid mediators have recently emerged as important factors in ALD pathogenesis. The current study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…13 A lipidomics approach was recently used to discriminate ALD stages based on changes in plasma levels of lipid species (eg, elevated levels of 13hydroxyoctadecadienoic acid, 9,10-dihydroxyoctadecenoate, and 12,13-dihydroxyoctadecenoate in moderate AH versus heavy drinkers with mild ALD). 14 Because the gut-liver axis plays an important role in ALD, metagenomics has been applied to elucidate microbial/bacterial changes contributing to the disease development/progression (eg, cytolysinpositive Enterococcus faecalis was identified as a pathogenic bacterium in clinical AH and successfully targeted in experimental AH 15 ). Certainly, omic studies have been invaluable for identifying biomarkers, novel mechanisms, and therapeutic targets for AC and AH.…”
mentioning
confidence: 99%
“…13 A lipidomics approach was recently used to discriminate ALD stages based on changes in plasma levels of lipid species (eg, elevated levels of 13hydroxyoctadecadienoic acid, 9,10-dihydroxyoctadecenoate, and 12,13-dihydroxyoctadecenoate in moderate AH versus heavy drinkers with mild ALD). 14 Because the gut-liver axis plays an important role in ALD, metagenomics has been applied to elucidate microbial/bacterial changes contributing to the disease development/progression (eg, cytolysinpositive Enterococcus faecalis was identified as a pathogenic bacterium in clinical AH and successfully targeted in experimental AH 15 ). Certainly, omic studies have been invaluable for identifying biomarkers, novel mechanisms, and therapeutic targets for AC and AH.…”
mentioning
confidence: 99%
“…Therefore, it is feasible that decreased ABCB10 function resulted in the release of a higher quantity of irreversibly oxidized lipids and protein-adducts from hepatocytes to activate the initiation of NET formation in infiltrated neutrophils. Consistent with this interpretation, high oxylipins content in liver correlates with the severity of AH [ [25] , [26] , [27] ] and are potent inducers of NET formation as well [ [28] , [29] , [30] ]. We are currently setting up an in vitro system to determine which of these two possibilities can explain how increased ABCB10 function in hepatocytes mitigates NET formation in neutrophils in livers with AH.…”
Section: Discussionmentioning
confidence: 77%
“…Notably, the overexpression of CYP2J2 in FHD-mice not only elicited reduced inflammatory responses but also exhibited a significantly decreased in plasma triglyceride levels and liver lipid accumulation [ 27 ]. Furthermore, CYP2C-derived EpOMEs, EEQs, and EDPs are also known as important epoxides which reduce inflammation and autophagy in liver [ 28 , 29 ]. In fact, our research has revealed that SNL-fed db / db mice exhibited a significant decrease in the levels of hepatic triglyceride and the expression of inflammatory marker gene monocyte chemotactic protein 1 ( Mcp1 ), also known as Ccl2 , which is one of the 18 SNL-dependent down-regulated genes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%